2019
DOI: 10.3390/medicina55090607
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Micro-RNAs: The Most Recent and Relevant Biomarkers in the Early Diagnosis of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a frequently encountered cancer type, and its alarming incidence is explained by genetic and epigenetic alterations. Epigenetic changes may represent diagnostic and prognostic biomarkers of HCC. In this review we discussed deoxyribonucleic acid (DNA) hypomethylation, DNA hypermethylation, and aberrant expression of small non-coding ribonucleic acid (RNA), which could be useful new biomarkers in the early diagnosis of HCC. We selected the articles on human subjects published in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…2b). To cover the CpGs associated with HCC as much as possible, other CpGs suitable for HCC detection were also included in our analysis, according to previous studies [29][30][31][32][33][34][35][36]. Finally, we designed a probe panel covering 1595 CpGs for subsequent analysis.…”
Section: Methylation Marker Selection and Targeted Em-seqmentioning
confidence: 99%
“…2b). To cover the CpGs associated with HCC as much as possible, other CpGs suitable for HCC detection were also included in our analysis, according to previous studies [29][30][31][32][33][34][35][36]. Finally, we designed a probe panel covering 1595 CpGs for subsequent analysis.…”
Section: Methylation Marker Selection and Targeted Em-seqmentioning
confidence: 99%
“…Few studies address the impact of NO production or NOS expression and changes in DNA methylation patterns. COX2 activity is enhanced by NOS2-derived NO, which promotes angiogenesis and cell differentiation [37][38][39] and tumor growth, invasion and metastasis potential [40][41][42]. Hence, the assessment of the correlation between COX2 and NOS2 expression and microvessel density in HCV-positive HCCs suggested its importance in the pathogenesis of the disease [43].…”
Section: No and Dna Methylationmentioning
confidence: 99%
“…Epigenetic alterations due to iron overload have also been implicated in hepatocarcinogenesis. Epigenetic defects such as increased DNA methylation commonly occur in HCC [114] . Lehmann et al [115] found 84% of the non-cancerous liver biopsies derived from HH patients exhibited hypermethylation of genes that are often hypermethylated in HCC.…”
Section: Mechanisms Of Iron Toxicity In Hh Leading To Hccmentioning
confidence: 99%